Utility of Transmission Electron Microscopy in Small Round Cell Tumors - Na Rae Kim; Seung Yeon Ha; Hyun Yee Cho (Korean Society of Pathologists & the Korean Society for Cytopathology, 2015)
Small round cell tumors (SRCTs) are a heterogeneous group of neoplasms composed of small, primitive, and undifferentiated cells sharing similar histology under light microscopy. SRCTs include Ewing sarcoma/peripheral neuroectodermal tumor family tumors, neuroblastoma, desmoplastic SRCT, rhabdomyosarcoma, poorly differentiated round cell synovial sarcoma, mesenchymal chondrosarcoma, small cell osteosarcoma, small cell malignant peripheral nerve sheath tumor, and small cell schwannoma. Non-Hodgkin's malignant lymphoma, myeloid sarcoma, malignant melanoma, and gastrointestinal stromal tumor may also present as SRCT. The current shift towards immunohistochemistry and cytogenetic molecular techniques for SRCT may be inappropriate because of antigenic overlapping or inconclusive molecular results due to the lack of differentiation of primitive cells and unavailable genetic service or limited moleculocytogenetic experience. Although usage has declined, electron microscopy (EM) remains very useful and shows salient features for the diagnosis of SRCTs. Although EM is not always required, it provides reliability and validity in the diagnosis of SRCT. Here, the ultrastructural characteristics of SRCTs are reviewed and we suggest that EM would be utilized as one of the reliable modalities for the diagnosis of undifferentiated and poorly differentiated SRCTs.